INCLUSIVE RECRUITMENT PRACTICES FOR PEOPLE WITH DISABILITIES: A QUALITATIVE STUDY IN THE INFORMAL SECTOR - Berliana Dian Permatasari; Herry Widyastono; Subagya Subagya (Pusat Studi Difabilitas (PSD) LPPM Universitas Sebelas Maret, 2025)
The recruitment, selection, and training processes are key components in developing a professional workforce. Recruitment plays a crucial role in determining the quality of prospective employees in a company. Every individual has the right to work, including persons with disabilities. This study aims to explain the recruitment system for employees with disabilities at Barokah Motor in Ngawi. This research employed a qualitative method with a case study approach. The sample was selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation. Data validity was ensured through triangulation of sources, techniques, and time. The data were analysed using the interactive model, including data reduction, data display, conclusion drawing, and verification. The results show that Barokah Motor practices affirmative action for employees with disabilities by allocating one position per branch. The recruitment system for employees with disabilities at Barokah Motor follows the same procedural steps as that for other applicants.